Characterisation of KrishSupra-P Distribution and Its Biomedical Application - Praseeja, C. B.; Prasanth, C. B.; Subramanian, C.; Unnikrishnan, T. (Communications in Mathematics and Applications, 2024)
In this article, an innovative generalization of Sauleh distribution is considered and named it as KrishSupra-P Distribution (KSPD). Its several statistical properties were discussed and the model parameters are predicted using the Maximum Likelihood Estimation (MLE) approach. The model’s biomedical application using a real data set is discussed and contrasted with some other famous distributions.